2019
DOI: 10.1186/s13104-019-4636-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic detection of metallo-β-lactamases in A. baumanii isolates obtained from clinical samples in Shahrekord, southwest Iran

Abstract: Objective Acinetobacter baumanii is a pathogenic bacterium that is the cause of many nosocomial infections. This study aimed to determine metallo-β-lactamases (MBL) produced by the A. baumanii isolates obtained from clinical samples in Shahrekord, southwest Iran. Results A total of 100 A. baumanii were isolated from 250 clinical samples between June 2013 and June 2014. Then, the isolates were identified by biochemical tests, and MBL … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In this study, carbapenem mediated resistance was mainly found due to class B and class D carbapenemase. Among class B bla IMP and bla VIM the results are in concordance with other studies, 23,24 while in some studies [25][26][27][28] lower percentage of isolates harbouring bla IMP gene was observed. These variations were found due to change in pattern of resistance over different years and geographical difference within the countries over a period.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, carbapenem mediated resistance was mainly found due to class B and class D carbapenemase. Among class B bla IMP and bla VIM the results are in concordance with other studies, 23,24 while in some studies [25][26][27][28] lower percentage of isolates harbouring bla IMP gene was observed. These variations were found due to change in pattern of resistance over different years and geographical difference within the countries over a period.…”
Section: Discussionsupporting
confidence: 89%
“…Acinetobacter baumannii is an important opportunistic pathogen causing about 80% of clinical infections of the 21 st century (Odewale, Adefioye, Ojo, Adewumi, & Olowe, 2016;Almasaudi, 2018;Khaledi et al, 2019), and several nosocomial infections such as ventilator-associated infection (VAP), burn and wound infections leading to significant morbidity and mortality particularly in immunocompromised patients as well as those admitted in intensive care units (Basri et al, 2015;Azimi, Talebi, Pourshafie, Owlia, & Lari, 2015;Asif, Alvi, & Rehman, 2018). Report showed that, the A. baumannii has been isolated from blood, sputum, skin, pleural fluid, and urine samples, usually in device associated infections (Mayasari & Siregar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Acinetobacter baumannii possesses many properties that might lead to drug resistance. The main resistance mechanisms include the production of antimicrobial inactivating enzymes, such as beta-lactamases and amino-glycosidase (8,9), changing the target position and reducing membrane permeability, biofilm formation, and high expression of efflux pumps, particularly those with resistance nodulation cell division (RND) transporters (8,10,11).…”
Section: Introductionmentioning
confidence: 99%